2018
DOI: 10.1038/s41395-018-0156-y
|View full text |Cite
|
Sign up to set email alerts
|

Needleless Transcutaneous Electrical Acustimulation: A Pilot Study Evaluating Improvement in Post-Operative Recovery

Abstract: Needleless TEA improves major postoperative symptoms by enhancing vagal and suppressing sympathetic activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 56 publications
2
59
0
Order By: Relevance
“…The main features of TEA include the use of selective acupoints, use of optimized parameters and improvement in autonomic functions(15, 18–22). Clinical studies have confirmed the therapeutic effect of TEA on a variety of GI motility disorders, such as gastro‐esophageal reflux diseases (GERD), functional dyspepsia (FD), constipation, chemotherapy‐induced nausea and vomiting, and so on(15, 18–22). TEA has been shown effective in treating functional constipation and constipation secondary to other reasons, such as stroke(15, 19, 23).…”
Section: Introductionmentioning
confidence: 99%
“…The main features of TEA include the use of selective acupoints, use of optimized parameters and improvement in autonomic functions(15, 18–22). Clinical studies have confirmed the therapeutic effect of TEA on a variety of GI motility disorders, such as gastro‐esophageal reflux diseases (GERD), functional dyspepsia (FD), constipation, chemotherapy‐induced nausea and vomiting, and so on(15, 18–22). TEA has been shown effective in treating functional constipation and constipation secondary to other reasons, such as stroke(15, 19, 23).…”
Section: Introductionmentioning
confidence: 99%
“…A special amplifier with a recording frequency of 100 Hz (model 2283 Fti Universal Fetrode Amplifier; UFI, Morro Bay, CA) was used to record the ECG signal from cutaneous electrodes: (a) The dog's skin where electrodes were to be placed was cleaned with special skin‐prep gel (Nuprep; Weaver and Company, Aurora); (b) conductive gel (Ten20; Weaver and Company, Aurora) was applied to reduce electrode‐skin impedance; and (c) three regular ECG electrodes were placed at the apical, the inside of the right hind leg, and the offside of the apical . After the deletion of the recording with severe motion artifacts due to occasional movement of the animal, the heart rate variability (HRV) signal was derived using a custom‐made software by identifying R peaks and calculating consecutive RR intervals from the ECG; then, the power spectrum analysis of the HRV signal was performed to calculate the power in different frequency bands . The power in the low‐frequency (LF) band (0.04‐0.15 Hz) reflects mainly sympathetic activity, whereas the power in the high‐frequency (HF) band (0.15‐0.50 Hz) stands purely parasympathetic or vagal activity .…”
Section: Methodsmentioning
confidence: 99%
“…After the deletion of the recording with severe motion artifacts due to occasional movement of the animal, the heart rate variability (HRV) signal was derived using a custom‐made software by identifying R peaks and calculating consecutive RR intervals from the ECG; then, the power spectrum analysis of the HRV signal was performed to calculate the power in different frequency bands . The power in the low‐frequency (LF) band (0.04‐0.15 Hz) reflects mainly sympathetic activity, whereas the power in the high‐frequency (HF) band (0.15‐0.50 Hz) stands purely parasympathetic or vagal activity . In this study, the standardized values were used, that is, LF was defined as LF/(HF + LF) and HF as HF/(HF + LF) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The newly developed transcutaneous electrical acustimulation (TEA) is a noninvasive and needleless method, with electrical stimulation delivered to acupoints via surface electrodes and is well accepted by patients . According to a few recent preliminary studies, TEA at ST36 and PC6 seems able to improve symptoms and motility in patients with GERD , FD , and postsurgical recovery . It has been reported that TEA can improve the symptoms of dyspepsia by enhancing vagus nerve activity and inhibiting sympathetic nerve activity .…”
Section: Introductionmentioning
confidence: 99%